2015
DOI: 10.3136/fstr.21.615
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Extraction Conditions with Ultrasound for Anti-hyperglycemic Activities from <i>Psidium guajava</i> Leaf

Abstract: The present study evaluated the optimal parameters for Psidium guajava leaf extraction by ultrasound to obtain maximal anti-hyperglycemic activities in the extract. The response surface methodology was employed for empirical model building. The maximum inhibition of the two starch-digesting enzymes α-amylase and α-glucosidase was determined. The optimized extraction parameters of solvent-to-solid ratio, extraction time, and extraction temperature for obtaining the maximum inhibitory activity for 50 µg/mL extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The Pearson analysis showed that GIA had strong positive correlation with TPC (r = 0.92, p <0.05), indicating the TPC was responsible for the GIA. This finding was in agreement with Liu et al (2015) who reported that there was a strong correlation between GIA and TPC of guava leaves water extract.…”
Section: α-Glucosidase Inhibitory Activity (Gia)supporting
confidence: 93%
“…The Pearson analysis showed that GIA had strong positive correlation with TPC (r = 0.92, p <0.05), indicating the TPC was responsible for the GIA. This finding was in agreement with Liu et al (2015) who reported that there was a strong correlation between GIA and TPC of guava leaves water extract.…”
Section: α-Glucosidase Inhibitory Activity (Gia)supporting
confidence: 93%
“…After 10-week treatment, the metabolic syndrome status of high-fructosehigh-fat fed mice were ameliorated by high dose GvEx. Our previous study has demonstrated that GvEx could improve high-glucose induced insulin resistant conditions in mouse FL83B cells via enhancing the levels of signals involved in insulin transduction, including phospho-tyrosine of insulin receptor, phospho-tyrosine of insulin receptor substrate, p85 regulatory subunit of phospho-inositide 3 kinase, pAkt (Ser), Glut 2, and glycogen synthase (Liu et al, 2015a). These results were also confirmed in the present study by a diet-induced insulin resistant animal models.…”
Section: Effects Of Gvex On Lipid Metabolism In Experimental Animalssupporting
confidence: 88%
“…Homogenates were then centrifuged at 27,000 x g for 10 min at 4°C. The supernatant was isolated and immunoblotting and was performed as described previously (Liu et al, 2015a). The supernatant was used for the determination of protein abundance, including phospho-tyrosine of AMPK (p-AMPK (Thr)), phosphor-serine of protein kinase B (p-Akt (Ser)), PPAR-α, PPAR-γ, PPAR-δ, adiponectin, glucose transporter (Glut) 2, and Glut 4. β -Actin was used as an internal control to ensure adequate sample loading for all lands.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations